5A-Based Tourism and Local Economy: An Empirical Study of Koanara and Mulut Seribu, East Nusa Tenggara - Yuan Valentino Elim; Ratna Fitri Widyastuti; Roidah 'Afro'; Siti Khuzaifah; Charles C. Rambung; Abu Hasan Sangaji; Mariano A.T. Nugraha; Sirilus N.M. Lelan (Centre of Excellence in Tourism Udayana University, 2026)
This study analyzes the economic characteristics of local communities, the influence of 5A-based tourism development on local economic growth, and the environmental impacts of tourism activities in the Koanara and Mulut Seribu tourist destinations, East Nusa Tenggara Province, Indonesia. This study used a mixed-methods approach with a concurrent embedded design. Data were collected from 97 respondents through purposive sampling and 10 key informants through snowball sampling. Partial Least Squares (PLS) analysis with the SmartPLS 3.0 program was used to test five hypotheses regarding the influence of attractions, accessibility, accommodation, amenities, and awareness on community economic development. The results showed that local communities play a role as business owners (56%) and workers (44%), with 95% of business ownership coming from local residents. Most respondents reported increased income (80%) and improved family economic conditions (81%) after being involved in tourism businesses. The statistical test results prove that the five 5A components have a significant influence on the economic development of local communities (T-statistic > 1.96; p-value < 0.05), with the model able to explain 97.2% of the community's economic variance (R² = 0.972). The environmental impact analysis shows a more dominant positive influence, including improvements in physical infrastructure and socio-cultural preservation, although land conversion for accommodation and changes in social values ​​are important notes. These findings confirm that integrated tourism development based on 5A substantially contributes to local economic sustainability while still requiring strategic management to mitigate adverse environmental impacts.